A dosimetric evaluation of VMAT for the treatment of non‐small cell lung cancer. (1st September 2012) - Merrow, Caitlin E.; Wang, Iris Z.; Podgorsak, Matthew B.
Abstract : The purpose of this study was to demonstrate the dosimetric potential of volumetric‐modulated arc therapy (VMAT) for the treatment of patients with medically inoperable stage I/II non‐small cell lung cancer (NSCLC) with stereotactic body radiation therapy (SBRT). Fourteen patients treated with 3D CRT with varying tumor locations, tumor sizes, and dose fractionation schemes were chosen for study. The prescription doses were 48 Gy in 4 fractions, 52.5 Gy in 5 fractions, 57.5 Gy in 5 fractions, and 60 Gy in 3 fractions for 2, 5, 1, and 6 patients, respectively. VMAT treatment plans with a mix of two to three full and partial noncoplanar arcs with 5°–25° separations were retrospectively generated using Eclipse version 10.0. The 3D CRT and VMAT plans were then evaluated by comparing their target dose, critical structure dose, high dose spillage, and low dose spillage as defined according to RTOG 0813 and RTOG 0236 protocols. In the most dosimetrically improved case, VMAT was able to decrease the dose from 17.35 Gy to 1.54 Gy to the heart. The D 2 cm decreased in 11 of 14 cases when using VMAT. The three that worsened were still within the acceptance criteria. Of the 14 3D CRT plans, seven had a D 2 cm minor deviation, while only one of the 14 VMAT plans had a D 2 cm minor deviation. The R 50 % improved in 13 of the 14 VMAT cases. The one case that worsened was still within the acceptance criteria of the RTOG protocol. Of the 14 3D CRT plans, seven had an R 50 % deviation. Only one of the 14 VMAT plans had an R 50 % deviation, but it was still improved compared to the 3D CRT plan. In this cohort of patients, no evident dosimetric compromises resulted from planning SBRT treatments with VMAT relative to the 3D CRT treatment plans actually used in their treatment. PACS numbers: 87.50.‐a, 87.53.‐j, 87.55.‐x, 87.55.D‐, 87.55.dk, 87.55.de